Consideration of The Judge of The State Court of Surabaya in The Crime Of Racism - Evi Yufita; Zainal Arifin; Mahfud Fahrazi (Faculty of Law, Kadiri Islamic University (UNISKA) Kediri, 2022)
This study discusses the judge's considerations and progressive law in court decisions against defendants for racism crimes. Judges in their considerations and decisions have not fulfilled the aspects of justice and expediency. The purpose of this study is to analyze the judgments of the Surabaya District Court judges in imposing a sentence on the perpetrators of the crime of racism in the decision number 3147/Pid.Sus/2019/PNSby and to analyze the decision number 3147/Pid.Sus/2019/PNSby in terms of progressive legal theory. The method used in this research is normative juridical. The results of this study are the judge's consideration of the case decision number 3147/Pid.Sus2019/PNSby disagrees with the judge's considerations regarding the criminal conviction given to Syamsul Arifin as a defendant in a criminal act of racism. Based on the facts, Syamsul Arifin was proven guilty and one of the evidences was the circulation of a video stating that the defendant deliberately used the word